2021
DOI: 10.3390/beverages7030048
|View full text |Cite
|
Sign up to set email alerts
|

Kefir as a Functional Beverage Gaining Momentum towards Its Health Promoting Attributes

Abstract: The consumption of fermented foods posing health-promoting attributes is a rising global trend. In this manner, fermented dairy products represent a significant subcategory of functional foods with established positive health benefits. Likewise, kefir—a fermented milk product manufactured from kefir grains—has been reported by many studies to be a probiotic drink with great potential in health promotion. Existing research data link regular kefir consumption with a wide range of health-promoting attributes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 96 publications
0
31
0
1
Order By: Relevance
“…In particular, the consumption of industrial kefir and kombucha increased [15,25] and the latter was reported, in the magazine Forbes, as the drink of 2020 [26]. Although, as source of bioactive components that could be beneficial for human health, there is no evidence about systematic human trials being done using kombucha tea [27] and some toxicity related to kombucha consumption has been reported so far when kept in a ceramic pot for six months or in lead-glazed earthenware at refrigerator temperature [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the consumption of industrial kefir and kombucha increased [15,25] and the latter was reported, in the magazine Forbes, as the drink of 2020 [26]. Although, as source of bioactive components that could be beneficial for human health, there is no evidence about systematic human trials being done using kombucha tea [27] and some toxicity related to kombucha consumption has been reported so far when kept in a ceramic pot for six months or in lead-glazed earthenware at refrigerator temperature [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports established that the gut microbiota can be targeted and manipulated by suitable dietary means to prevent several temporary health issues and alleviate some diseases [ 8 ]. Researchers have confirmed that the gut microbiome can be improved by the intake of prebiotic supplements and through the consumption of functional food based on probiotics [ 9 ]. Probiotics and foods prepared with probiotics are generally considered safe.…”
Section: Influence Of Probiotics and Functional Foods On The Gut Micr...mentioning
confidence: 99%
“…The fermentation process is done by lowering the pH of the food, using microorganisms that convert the sugars present in the product into acid. It is most often accomplished with lactic acid bacteria (LAB), which produce lactic acid as the major product of carbohydrate metabolism [2][3][4][5][6]. Some microorganisms in this group also exhibit probiotic properties, and their consumption is beneficial to selected aspects of human health (e.g., gastrointestinal function, immunity) [7,8].…”
Section: Introductionmentioning
confidence: 99%